2005
DOI: 10.1124/mol.104.007013
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific Sorting of the ETAEndothelin Receptor by a Novel Endocytic Recycling Signal for G Protein-Coupled Receptors

Abstract: We have previously reported that endocytic sorting of ET A endothelin receptors to the recycling pathway is dependent on a signal residing in the cytoplasmic carboxyl-terminal region. The aim of the present work was to characterize the carboxylterminal recycling motif of the ET A receptor. Assay of truncation mutants of the ET A receptor with increasing deletions of the carboxyl-terminal tail revealed that amino acids 390 to 406 contained information critical for the ability of the receptor to recycle. This pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 42 publications
(68 reference statements)
2
51
0
Order By: Relevance
“…28 In addition to C-terminal PDZ ligands, one study has indicated that an internal PDZ ligand present in the ET A endothelin receptor C-tail can regulate receptor recycling. 29 Our study has also shown that the C-terminal ETPM motif of the P2Y 12 R, a type I PDZ motif, is required for receptor recycling. Deletion or mutation of this sequence leads to the accumulation of the receptor in an intracellular sorting compartment and blockade of receptor recycling.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition to C-terminal PDZ ligands, one study has indicated that an internal PDZ ligand present in the ET A endothelin receptor C-tail can regulate receptor recycling. 29 Our study has also shown that the C-terminal ETPM motif of the P2Y 12 R, a type I PDZ motif, is required for receptor recycling. Deletion or mutation of this sequence leads to the accumulation of the receptor in an intracellular sorting compartment and blockade of receptor recycling.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of VHS domains have been shown to bind to acidic diLeu motifs; however a direct interaction between the VHS domain of HRS and the acidic diLeu motif of the β 2 AR is unlikely because the VHS domain lacks the critical residues important for binding to acidic di-Leu D-X-X-L-L motifs (46,47). In addition to C-terminal PDZ ligands, one study has indicated that an internal PDZ ligand present in the ET A endothelin receptor Ctail can regulate receptor recycling (48), but the endocytic sorting machinery that mediates this process has not been identified. Interestingly, internal PDZ ligand sequences have also been identified in several other human GPCRs (48).…”
Section: Pdz Ligandsmentioning
confidence: 99%
“…In addition to C-terminal PDZ ligands, one study has indicated that an internal PDZ ligand present in the ET A endothelin receptor Ctail can regulate receptor recycling (48), but the endocytic sorting machinery that mediates this process has not been identified. Interestingly, internal PDZ ligand sequences have also been identified in several other human GPCRs (48).…”
Section: Pdz Ligandsmentioning
confidence: 99%
“…Caveolar structures cluster signaling molecules through caveolin and PDZ (postsynaptic density protein, Drosophila disc large tumor supressor, Zo-1 protein) domain proteins in a spatially confined subsarcolemmal region to make protein-protein interactions more rapid and efficient (34). A recent study (20) also suggests that internal PDZ ligand motif seems to regulate efficient recycling of the ET A endothelin receptor. Later, growing evidence suggested that caveolin-1 regulates the interaction of ET-1 with its receptors (37).…”
mentioning
confidence: 99%